2017
DOI: 10.3389/fmicb.2017.00095
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Interactions of Infant Bifidobacteria and Eubacterium hallii during L-Fucose and Fucosyllactose Degradation

Abstract: Fucosyllactoses (2′- or 3′-FL) account for up to 20% of human milk oligosaccharides (HMOs). Infant bifidobacteria, such as Bifidobacterium longum subsp. infantis, utilize the lactose moiety to form lactate and acetate, and metabolize L-fucose to 1,2-propanediol (1,2-PD). Eubacterium hallii is a common member of the adult gut microbiota that can produce butyrate from lactate and acetate, and convert 1,2-PD to propionate. Recently, a Swiss cohort study identified E. hallii as one of the first butyrate producers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 46 publications
10
150
1
1
Order By: Relevance
“…B. breve 24b grown as monoculture in fucose-containing medium produced 1,2-propanediol as a fermentation product (Fig. 5C), confirming previous observations of this species (17). However, 1,2-propanediol was not detected in steady-state 2FL cocultures.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…B. breve 24b grown as monoculture in fucose-containing medium produced 1,2-propanediol as a fermentation product (Fig. 5C), confirming previous observations of this species (17). However, 1,2-propanediol was not detected in steady-state 2FL cocultures.…”
Section: Resultssupporting
confidence: 89%
“…Fucose is fermented to 1,2-propanediol by Bifidobacterium longum subspecies infantis and B. breve (17). The production of 1,2-propanediol by B. breve from fucose in batch culture but its absence in chemostat coculture with B. bifidum indicated that it might be used as a growth substrate by the latter species (a quid pro quo for fucose/lactose).…”
Section: Discussionmentioning
confidence: 99%
“…Quantified metabolic products indicates that fucose, acetate, pyruvate, and 1,2-propanediol are liberated from HMO degradation and could potentially function as candidates for cross-feeding. However, we did not see evidence of metabolism of these compounds by the B. longum strain as has been reported with other members of the infant microbiota; such as the 2′FL metabolic end product 1,2-propanediol which drives cross-feeding interactions between B. infantis and Eubacterium halli [52]. Recent work suggests that extracellular sialidases are the main source of crossfeeding interactions between bifidobacterial strains, as has been described for B. longum, which by producing sialylated carbohydrates and free sialic acid promotes B. breve growth [38,39].…”
Section: Discussioncontrasting
confidence: 57%
“…Both butyric acid and propionate are important for gut health as they can interact with host epithelium to stimulate mucin release, increase mucosal blood flow and modulate the immune system (Pl€ oger et al 2012;Reichardt et al 2014). Schwab and colleagues (Schwab et al 2017) found a trophic interaction between Bifidobacteria and Eubacterium hallii (E. hallii), a common member of the adult gut microbiota, during L-fucose degradation. In a single culture E. hallii was not able to grow on L-fucose.…”
Section: Effects Of Hmos On Microbiota Compositionmentioning
confidence: 99%